2018
DOI: 10.1155/2018/3947626
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Two Polymorphisms of ERCC2, rs13181 and rs1799793, in Clinical Outcomes of Chemotherapy in Gastric Cancer Patients: A Meta-Analysis

Abstract: Background Several researchers have investigated the relationship between ERCC2 rs13181 and rs1799793 polymorphisms and chemotherapy efficacy in terms of tumour response and prognosis in gastric patients. However, the published data have shown inconsistencies. Methods PubMed, Elsevier, and Chinese National Knowledge Infrastructure databases were searched for relevant articles published before August 1, 2017. Thirteen studies including 3096 gastric cancer patients treated with chemotherapy were included. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Various genetic factors are predicted to affect treatment efficiency and prognosis in patients with HCC, such as X-ray cross-complementing group 1 ( XRCC1 ), X-ray repair cross-complementing group 3 ( XRCC3 ), and excision repair cross-complementation group 2 ( ERCC2 ). Many previous studies have investigated the associations between polymorphisms in these genes and prognosis [47]. In 2012, Jung et al [8] found that XRCC1 rs25487, ERCC5 rs2018836, ERCC5 rs3818356, and XRCC4 rs1805377 have significant effects on survival.…”
Section: Introductionmentioning
confidence: 99%
“…Various genetic factors are predicted to affect treatment efficiency and prognosis in patients with HCC, such as X-ray cross-complementing group 1 ( XRCC1 ), X-ray repair cross-complementing group 3 ( XRCC3 ), and excision repair cross-complementation group 2 ( ERCC2 ). Many previous studies have investigated the associations between polymorphisms in these genes and prognosis [47]. In 2012, Jung et al [8] found that XRCC1 rs25487, ERCC5 rs2018836, ERCC5 rs3818356, and XRCC4 rs1805377 have significant effects on survival.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA helicase encoded by the excision repair cross-complementing group 2 gene (ERCC2), also called xeroderma pigmentosum group D (XPD), is involved in basal cellular transcription and NER of DNA lesions [51]. To date, a number of studies have implicated the role of genetic polymorphism within ERCC2 gene in various cancers, such as gastric, pancreatic, glioma, bladder, and hepatocellular carcinoma [52][53][54][55][56][57]. The most studied polymorphisms rs13181 (Lys751Gln) and rs238406 (Arg156Arg) were demonstrated to alter the function of encoded protein, and, in consequence, influence on DNA repair capacity [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of these changes is related to the clinical outcome of chemotherapy's effectiveness, such as decreased response and survival. 99,100 In contrast to ABCC2, which is one of the MRP transporter families that encodes Multidrug Resistance-associated Protein 2, it functions as an organic anion transporter, playing a role in platinum-conjugated transport out of cells. C>T polymorphisms (rs717620) are associated with altered ABCC2 expression or function.…”
Section: Discussionmentioning
confidence: 99%